Pengaruh Perilaku Berwirausaha Terhadap Kinerja Usaha Mikro Kecil Sektor Kuliner Di Kecamatan Pamona Puselemba Kabupaten Poso - Olviyana Mainti; Silvany Annajde Taariwuan; Olvit Olniwati Kayupa; Fredrik Bastian Kawani; Feliks Arfid Guampe (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The aim of this study is to explore the influence of entrepreneurial behavior on the performance of Small Micro Enterprises (SMEs) in the culinary sector in Pamona Puselemba District, Poso Regency. The research was conducted from August to September 2023, using a sample of 40 culinary SME operators, selected through purposive sampling from a total population of 76 businesses. Data collection methods included observation and questionnaires, designed to measure aspects of entrepreneurial behavior and business performance. Data analysis was conducted using validity tests, reliability tests, simple linear regression, and coefficient of determination tests. The results indicate that entrepreneurial behavior has a positive and significant effect on business performance, as evidenced by a positive regression coefficient between the entrepreneurial behavior variable and business performance. The coefficient of determination value shows that entrepreneurial behavior can explain about 16.1% of the variability in business performance, with the remaining variability explained by other factors outside the study. Based on these findings, it is recommended that SME operators in the culinary sector in the study area enhance their entrepreneurial behavior to achieve improved business performance. This recommendation is supported by the need for government policies and academic institution support in the form of additional capital and entrepreneurship training.